A 39-Year-Old Male Congenital Tricuspid Atresia Patient Who Presented with a New Axillary Lesion after an Orthotopic Heart Transplant - Zizi Yu; Nicholas Theodosakis; Megan J. Fitzpatrick; Ruth K. Foreman; Bonnie Mackool (MDPI AG, 2019)
Mucormycosis is a rare and aggressive fungal infection, most often caused by species of the Mucor, Rhizomucor, Rhizopus, Absidia, and Cunninghamella genera. The condition most commonly affects patients with uncontrolled diabetes, HIV/AIDS, malignancy, and those receiving long-term immunosuppressive therapy. We report the case of a 39-year-old male with biopsy-proven cutaneous mucormycosis of the left axilla 4 months after an orthotopic heart transplant for congenital tricuspid atresia.